Perioperative Management of a Pediatric Patient with Beckwith-Wiedemann Syndrome Undergoing a Partial Glossectomy According to Egyedi/Obwegeser - Antonio Izzi; Vincenzo Marchello; Aldo Manuali; Lazzaro Cassano; Andrea Di Francesco; Annalisa Mastromatteo; Andreaserena Recchia; Maria Pia Tonti; Grazia D'Onofrio; Alfredo Del Gaudio (MDPI AG, 2023)
Here, we report the perioperative management of a clinical case of a 6 year, 5 month old girl suffering from Beckwith-Wiedemann syndrome undergoing a partial glossectomy procedure in a patient with surgical indication for obstructive sleep apnea syndrome (OSAS), difficulty swallowing, feeding, and speech. On surgery day, Clonidine (4 µg/kg) was administered. Following this, a general anesthesia induction was performed by administering Sevoflurane, Fentanyl, continuous intravenous Remifentanil, and lidocaine to the vocal cords, and a rhinotracheal intubation with a size 4.5 tube was carried out. Before starting the procedure, a block of the Lingual Nerve was performed with Levobupivacaine. Analgosedation was maintained with 3% Sevoflurane in air and oxygen (FiO2 of 40%) and Remifentanil in continuous intravenous infusion at a rate of 0.08-0.15 µg/kg/min. The surgical procedure lasted 2 h and 32 min. At the end of the surgery, the patient was under close observation during the first 72 h. In the pediatric patient with Beckwith-Wiedemann syndrome submitted to major maxillofacial surgery, the difficulty in managing the airways in the preoperative phase during intubation and in the post-operative phase during extubation should be considered.